Eating from the tree that causes insight: an investigation of the presence of wisdom in the paradise and fratricide narratives - Hamilton, Valerie Tonyan (2023)
This work examines the presence of wisdom as a theme within the Paradise and Fratricide narratives of the Hebrew Bible (Genesis 2:4–3:24). As the nature of “wisdom” in the Paradise Narrative is not agreed upon by interpreters, one goal of this work is to offer a more precise definition of wisdom as a theme in this account. A second goal is to ascertain whether this wisdom theme in the Paradise Narrative continues into the Fratricide Narrative. The analysis begins by examining literary historical issues in the Paradise and Fratricide narratives, and the conclusions of this chapter form the starting point for the rest of the study. The symbols/motifs in the Paradise and Fratricide narratives that have a potential association with wisdom are then considered in two ways. First, the use of the symbol/motif within the narratives themselves is examined. Secondly, the use of the symbols/motifs in outside sources (especially “wisdom literature”) is reviewed, followed by consideration of whether there is a connection between these outside occurrences and the use of the symbol/motif in the Paradise and Fratricide narratives. It is concluded that the type of wisdom featured in the Paradise Narrative is not strongly related to the discussion of wisdom within the “wisdom literature” of the Hebrew Bible. Instead, the supposed “wisdom” theme in the Paradise Narrative has to do with the knowledge of good and bad, which is a characteristic associated with maturity and social influence. It is argued that this same kind of “wisdom” is also in focus within the following account, the Fratricide Narrative. These conclusions imply that it is imprecise to refer to the Paradise and Fratricide narratives as “wisdom literature” or as literature influenced by the wisdom tradition. Furthermore, the connection between the Paradise and Fratricide narratives is strengthened by defining this shared theme, suggesting that these stories should be understood as a literary unit.